2015
DOI: 10.1007/s12160-015-9703-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Avoidance of Skin Damage Feedback Among College Students

Abstract: Background-Showing people a personal ultraviolet (UV) photograph depicting skin damage can be an effective method for changing sun protection cognitions and behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Recent evidence indicates that the drive to seek information might be asymmetric, with people exhibiting a preference for positive over negative belief updating, such that humans are more curious about positive than negative information (Charpentier et al, 2018;Marvin & Shohamy, 2016). In fact, CURIOSITY IS MODULATED BY UNCERTAINTY AND VALENCE 4 human volunteers have been shown to be willing to pay for ignorance about negative information (Charpentier et al, 2018), consistent with the observation that people often prefer not to be informed about potential negative medical test results (Dwyer, Shepperd, & Stock, 2015;Persoskie, Ferrer, & Klein, 2014). Such preference of knowledge about advance positive outcomes (versus ignorance of negative outcomes) has been argued to arise because reward prediction errors carried by such knowledge can boost the anticipation of positive versus negative outcomes (Iigaya, Story, Kurth-Nelson, Dolan, & Dayan, 2016) These observations led us to ask whether the drive to update our world model depends on the valence of the information gap, with greater curiosity for greater positive information gaps, but reduced curiosity for greater negative information gaps.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recent evidence indicates that the drive to seek information might be asymmetric, with people exhibiting a preference for positive over negative belief updating, such that humans are more curious about positive than negative information (Charpentier et al, 2018;Marvin & Shohamy, 2016). In fact, CURIOSITY IS MODULATED BY UNCERTAINTY AND VALENCE 4 human volunteers have been shown to be willing to pay for ignorance about negative information (Charpentier et al, 2018), consistent with the observation that people often prefer not to be informed about potential negative medical test results (Dwyer, Shepperd, & Stock, 2015;Persoskie, Ferrer, & Klein, 2014). Such preference of knowledge about advance positive outcomes (versus ignorance of negative outcomes) has been argued to arise because reward prediction errors carried by such knowledge can boost the anticipation of positive versus negative outcomes (Iigaya, Story, Kurth-Nelson, Dolan, & Dayan, 2016) These observations led us to ask whether the drive to update our world model depends on the valence of the information gap, with greater curiosity for greater positive information gaps, but reduced curiosity for greater negative information gaps.…”
Section: Introductionmentioning
confidence: 64%
“…Here, we examined whether this positive relationship between information gap and curiosity depends on whether the outcome will contain good or bad news. It has been reported that humans tend to avoid negative information, presumably because such knowledge boosts the anticipation of negative outcomes (Charpentier et al, 2018;Dwyer et al, 2015;Golman, Hagmann, & Loewenstein, 2017;Karlsson, Loewenstein, & Seppi, 2009;Persoskie et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Information avoidance theorists emphasize psychological threatwhether emotional, cognitive, or behavioral-as the common mechanism underpinning the decision to ''say no'' to available, but potentially unwanted, information (Sweeny & Miller, 2012). They have successfully applied this health information avoidance framework to predict screening avoidance behavior for a variety of health conditions including cancer and diabetes (Howell & Shepperd, 2013;van Koningsbruggen & Das, 2009), heart disease , and UV-related skin damage (Dwyer et al, 2015).…”
Section: Health Information Avoidancementioning
confidence: 99%
“…Upon completion of this questionnaire, the experimenter informed them that they would be completing the partner task at the end of the session and that they would finish up on the computer first with the second experiment. This "second experiment" contained the actual measures of interest and was based on a modified procedure from Dwyer et al (2015) (such that everyone might be interested in seeing the photo), this message also contained a "disclaimer" that indicated that seeing these photos makes people aware of underlying skin damage that they were likely unaware of beforehand and that this experience can be unpleasant. Participants who choose not to see the UV photograph would be said to be engaging in information avoidance.…”
Section: Methodsmentioning
confidence: 99%
“…They consistently found that the more threat management resources a person had (both personal and interpersonal), the less likely they were to avoid information about their health. However, in the context of information avoidance studies, threat management resources have always been measured and never directly manipulated making it difficult to draw causal conclusions (e.g., Dwyer, Shepperd, & Stock, 2015;Melnyk & Shepperd, 2012).…”
Section: Relevant Moderators Of Information Avoidancementioning
confidence: 99%